RAW MATERIAL DEWATERING ELECTROMAGNETIC TECHNOLOGIES - Burdo O.G.; Terziev S.G.; Yarovoi I.I.; Borshch A.A. (Problems of the Regional Energetics)
Moisture transfer schemes and mechanisms of capillary-porous materials dehydration are considered. Mechanical, thermal and diffusive mechanisms for different moisture linkage forms are analyzed, driving forces and velocity coefficients of processes are estimated. Availability of dehydration in microwave frequencies range field is shown. A new generalized complex that takes into account a specificity of micro- and nanokinetics of moisture transfer in products is proposed. The explanation of barodiffusive moisture transfer process mechanism in a product is shown. The results of experimental researches, in which specific energy of 1,9 MJ per 1 kg of removed moisture is reached, are shown. The tests results of the band dryer with microwave and infrared energy generators are presented.